The Effectiveness of Expressive Writing Therapy in Reducing Stress Levels in Young Adult Women Victims of Sexual Violence in Dating Relationships (Dating Violence) in Bandung City - Kristia Violita Permana; Hedi Wahyudi; Indri Utami Sumaryanti (Eduvest - Journal of Universal Studies, 2024)
In courtship or commonly referred to as KDP or (Dating Violence). After experiencing KDP, then you feel a physiological psychological awakening and behavior such as not feeling positive feelings, feeling hopeless, feeling worthless, excessive fear, anxiety, unable to concentrate, sensitive to small things, difficulty feeling calm, restless, etc. thus causing stress. This research was conducted on three subjects who experienced sexual violence in dating (Dating Violence). The subject cannot solve the problem within himself and cannot overcome the stress he is experiencing. So that the symptoms of stress appear, such as psychological, physiological and behavioral symptoms that appear. To overcome and help with this problem, researchers want to see how effective Expressive writing therapy (EWT) is to reduce the degree of stress in women who experience sexual violence in dating (Dating Violence). The measuring tool used is the Lovibond stress scale which consists of 42 statements which include three aspects, physiological aspects, psychological aspects and behavioral aspects. The research method used was experimental in the form of a one group pre test post test design. The results of the pre test-post test showed a decrease in the degree of stress by 46.40%. Thus the research hypothesis which reads "Expressive writing therapy (EWT) is said to be effective in reducing the degree of stress in early adult women who experience Dating Violence if the degree of stress during the post-test is smaller than the pre-test is proven.